Tracing the origins of learning difficulties - Sibanda, Patrick (Pure and Applied Science Advances, 2017)
The paper focuses on tracing the origins of learning difficulties with the view of laying a foundation for their mitigation. While learning difficulties are variously understood, this paper argues for a conceptualization that differentiates them from learning disabilities. Therefore, the endogenous and exogenous originating factors of learning difficulties that are examined in this paper are aligned to the conceptualization that learning difficulties are temporary and can therefore be minimized or eliminated as a function of usage of appropriate intervention. The paper, however, acknowledges that the major sources of learning difficulties are of organic origin and thus endogenous. For the exogenous originating factors, schools have a direct role to play but can only be effective if they forego the traditional practice of ignoring the fact that schools and teachers are in effect part of the originators of learning difficulties. Thus, it can be concluded from this paper that, awareness of the origins of learning difficulties is the first concrete step toward minimizing or eliminating them and that the school plays a central role in these regards. To achieve a meaningful central role in minimizing or eliminating learning difficulties however, schools must be conscious of internal variables that cause learning difficulties and deal with them decisively before blaming or attending to other originating factors. In addition, they should be aware of and always look out for the general indicators of learning difficulties.